Quasi-Static and Dynamic Collapse Behavior of Circular Foam-Filled Tubes Inspired by Bamboos - Kai Liu; Zhenhao Yu; Kaiyun Wang; Lin Jing (Chinese Journal of Mechanical Engineering)
Abstract The axial collapse mechanical behavior and energy absorption characteristics of circular foam-filled tubes mimicking the bamboo characteristics under quasi-static and low-velocity impact loads were investigated via experiments and numerical simulations in this study. The crushing deformation process, load-displacement responses, the strain field and temperature field distribution characteristics of foam-filled tubes were explored. The energy absorption mechanism and crashworthiness performance of specimens were evaluated and compared with conventional empty tubes. Effects of ambient temperature on axial collapse behavior and crashworthiness indices were also clarified. The results revealed that the superior energy absorption capacity of foam-filled tubes was attributed to the strengthening effect of bionic joints and the filling effect of aluminium foam. The energy absorption (EA), specific energy absorption (SEA), and other crashworthiness indices of foam-filled tubes under axial impact load were greatly improved than that of quasi-static load. Compared to conventional empty tubes, the foam-filled tube had a larger energy-absorbing effectiveness factor under both quasi-static and dynamic loads. The increased temperature weakens the crashworthiness performance and energy absorption ability of the foam-filled tube. The SEA values ranged from 28.2 J/g to 22.1 J/g for the quasi-static load and 31.9 J/g to 26.3 J/g for the dynamic load when the temperature elevated from −50 ℃ to 100 ℃.